Central Mali: Study of traditional livestock systems of the Niger Delta and the Sahel. Constraints and indications for research - International Livestock Centre for Africa (International Livestock Centre for Africa, 1978)
Presents a study of traditional livestock systems of the Niger delta and the Sahel. Identifies constraints to production in traditional systems and constraints to adequate analysis and quantitative identification to problems. Outlines research requirements and gives indications of development possibilities.